(untitled) (Archives of Criminology, 2008)
The text discusses the changes in penal policy in England and Wales in the United Kingdom that took place between 1970 and 2005. The background to the considerations presented in the article is the shift that took place in British penal policy in the 1990s. The model of the British penal policy discussed by the author was then characterised by a lengthening of the prison isolation of repeat and dangerous offenders, which resulted in an increase in the prison population and a simultaneous decrease in the crime rate. Andrzej Adamski guides the reader through the various stages of change and the evolution of penal policy in the United Kingdom in the selected years. In order to illustrate his thoughts, the author provides graphs showing the prison population in England and Wales in the period 1975–2005. The text outlines individual stages, reflecting changes such as the ‘deadlock strategy’ between 1975 and 1979, the two-track penal policy of the Conservatives between 1979 and 1992, and the increase in the repressiveness of the British penal system after 1993. The study also includes the characteristics of the contemporary system of punishment in England and Wales and a breakdown of the sentences imposed in the British system. In the conclusion, Adamski tries to compare the penal policy in England and Wales with other countries of Western Europe. He emphasises that the British justice system is characterised by harsh treatment of offenders and imposing prison sentences. Among the sources of this growing tendency for stringency in British countries, the author points to the development of social neoliberalism, which is also raised by other researchers of the subject. According to him, the shape of penal policy and the level of repressiveness are mostly influenced by the political climate at a given moment.